Assisted sexual reproduction of Acropora cervicornis for active restoration on Florida’s Coral Reef - Koch, Hanna R.; Matthews, Briana; Leto, Celia; Engelsma, Cody; Bartels, Erich (Frontiers in Marine Science, 2022)
Given the rapid, global decline in the health and abundance of coral reefs, increased investments in restoration-based interventions -including asexual and sexual propagation- are being made by coral reef scientists at research institutions, but also at zoos and aquariums. Mote Marine Laboratory & Aquarium is an independent, non-profit marine science organization dedicated to the conservation and restoration of Florida’s Coral Reef, and does so, using science-based strategies. In order to promote the long-term persistence, resilience, and adaptive potential of restored coral populations on Florida's Coral Reef, Mote scientists are performing critical research and restoration activities related to assisted sexual reproduction (ASR). The objective of this study was to optimize ASR of Acropora cervicornis by (1) evaluating broodstock compatibility for genets actively used within Mote's restoration gene pool, (2) optimizing larval settlement by testing spectral cues, (3) and optimizing the grow-out of sexual recruits by testing the impact of light on growth, survival, and algal symbiont uptake in the presence of adult corals or not. Overall, we found that corals and genets spawned with high synchrony, both within and across years, and in terms of predicted spawning times related to nights after the full moon and minutes after sunset. Across two years, overall fertilization success was high (~95%), but we did find one pair of genets that was not compatible. During settlement, larvae preferred pink and purple-colored substrates, which was consistent with our expectation that they would select substrates similar in color to crustose coralline algae (CCA). Interestingly though, they only did so when a matching chemical cue from CCA was also present, indicating that larvae integrate multiple cues simultaneously to determine the most appropriate place to settle. Growth and symbiont uptake were faster in recruits reared in the presence of adult corals and additional lighting, but survivorship was not different through the first ten weeks post-settlement between treatments. A subset of corals was outplanted using two different techniques based on single or clustered outplants. We report the initial 1-month survival results. We also provide a detailed protocol and general recommendations for ASR based on years of coral sexual propagation experience.